Captivity and geography influence the antibiotic resistome of non-human primates - Huang, Hongli (Frontiers in Veterinary Science, 2022)
Background: Antibiotic resistance poses a serious threat for animals and humans health worldwide. Yet a comprehensive exploration of the influence factors of antibiotic resistance remains incomplete. Methods: Firstly, 97 metagenomic sequencing datasets of four species of monkeys were downloaded from the NCBI SRA(https://www.ncbi.nlm.nih.gov/sra/?term=) and 34 datasets of Macaca in our previous research were included. Secondly, we divided the datasets into four group according to their lifestyles (captive, wild) and geography. ARGs-OAP pipeline was conducted to resistome annotation. Lastly, we compared the diversity index of antibiotic resistance genes (ARGs) abundance of four species of monkeys. PCA and heatmap were performed to cluster analysis according to host lifestyles and geography. LEfSe analysis was performed to find the biomarker ARGs related to lifestyles and geography. Results: We obtained 19 related resistance antibiotics and 325 ARGs in 131 samples. We found a significantly higher abundance and diversity index of ARGs in the captive monkey than in the wild but not for all of the samples. The biomarker-tracking of ARGs analysis identified key ARGs related to aminoglycoside resistance genes and tetracycline resistance genes. Our results suggest that captivity and geography changes associated with human activities can lead to marked changes in the ecology of non-human primate gut flora ARGs.